Relationship between chromosome 18q status and colorectal cancer prognosis: a prospective, blinded analysis of 280 patients. - Popat, S; Zhao, D; Chen, Z; Pan, H; Shao, Y; Chandler, I; Houlston, R (2007)
BACKGROUND: The relationship between chromosome 18q allelic imbalance (AI) and survival in colorectal cancer (CRC) is unclear, and study design may have contributed to inconsistent results previously reported. PATIENTS AND METHODS: Two hundred and eighty tumours from CRC patients participating in a molecular sub-study from a single multicentre trial of adjuvant intra-portal 5-fluorouracil were genotyped at 5 chromosome 18q microsatellite markers, blinded to clinical data and prospective to follow-up. The relationship between overall survival and AI was examined. RESULTS: Two hundred and fifty-five tumours were informative for AI. The overall rate of AI was 49%. AI was not associated with age, tumour site or size. There was no difference in five-year survival rate between patients with (60.0% SE 5.2%) and without AI (61.4% SE 5.0%), even after correcting for covariates (HR=1.17, 95%CI:0.79-1.74, p=0.4). CONCLUSION: Our data does not [corrected] support chromosome 18q AI as an important marker of survival in the adjuvant setting. It should not, therefore, be used outside clinical trials.